2018
DOI: 10.15803/ijnc.8.1_32
|View full text |Cite
|
Sign up to set email alerts
|

Complete Visibility for Mobile Robots with Lights Tolerating Faults

Abstract: We consider the distributed setting of N autonomous mobile robots that operate in LookCompute-Move (LCM) cycles and communicate with other robots using colored lights (the robots with lights model). We study the fundamental Complete Visibility problem of repositioning N robots on a plane so that each robot is visible to all others. We assume obstructed visibility under which a robot cannot see another robot if a third robot is positioned between them on the straight line connecting them. We are interested in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Di Luna et al [6] observed that their COMPLETE VISIBILITY algorithm for non-faulty robots can solve COMPLETE VISIBILITY tolerating a faulty robot if the faulty robot is in the perimeter of the convex hull formed by the initial configuration of the robots. Aljohani and Sharma [16] provided an algorithm that tolerates one faulty robot (irrespective of whether the faulty robot is in the interior or not) when robots have both-axis agreement in the semi-synchronous setting under rigid movements. The idea was to position all the robots on the corners of a convex hull except the faulty robot that may still be in the interior of the hull in the final configuration.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Luna et al [6] observed that their COMPLETE VISIBILITY algorithm for non-faulty robots can solve COMPLETE VISIBILITY tolerating a faulty robot if the faulty robot is in the perimeter of the convex hull formed by the initial configuration of the robots. Aljohani and Sharma [16] provided an algorithm that tolerates one faulty robot (irrespective of whether the faulty robot is in the interior or not) when robots have both-axis agreement in the semi-synchronous setting under rigid movements. The idea was to position all the robots on the corners of a convex hull except the faulty robot that may still be in the interior of the hull in the final configuration.…”
Section: Related Workmentioning
confidence: 99%
“…The idea was to position all the robots on the corners of a convex hull except the faulty robot that may still be in the interior of the hull in the final configuration. Aljohani and Sharma [16] also showed that COMPLETE VISIBILITY can be solved tolerating, at most, 2 faulty robots under certain assumptions on initial configurations. Recently, Poudel et al [17] assumed a weaker one-axis agreement and presented an algorithm for COMPLETE VISIBILITY in the asynchronous setting that can tolerate any number of faulty robots.…”
Section: Related Workmentioning
confidence: 99%
“…Namely, satisfying that for any exchanged information there should be a channel which does not pass through other entities. For some of these applied researches see for instance [1,2,8,15,31].…”
Section: Introductionmentioning
confidence: 99%
“…In fact this research was inspired by the delivery robots belonging to Starship Technologies [14] that deliver groceries to the inhabitants of cities including Milton Keynes, home of the Open University. For some related studies on robot mobility in computer science see [1, 2, 4]. We introduce a variant that describes the largest number of robots that can travel through a network such that each vertex of the network can be visited by a robot, while at every stage any pair of robots can see each other through any shortest path between their positions without being obstructed by another robot.…”
Section: Introductionmentioning
confidence: 99%